Paraparetic Guillain‐Barré syndrome: Extending the axonal spectrum. Issue 6 (26th November 2013) - Nagashima, Takahide; Kokubun, Norito; Shahrizaila, Nortina; Funakoshi, Kei; Hirata, Koichi; Yuki, Nobuhiro
Abstract There are few reports of the paraparetic variant of Guillain‐Barré syndrome, and its pathophysiology is not well understood. We report a patient presenting with acute paraparesis following diarrhea. Serial nerve conduction studies suggested primary axonal injury, and not demyelination, predominantly in the lower limbs compared with the upper limbs. There was serological evidence of recent Campylobacter jejuni infection and strongly positive immunoglobulin G anti‐GD1a antibodies. Paraparetic Guillain‐Barré syndrome is likely to represent a regional form of Guillain‐Barré syndrome, with a nosological position within the axonal subtype.